Andrés de Urdaneta and the return trip from Philippines to New Spain - Mira Toscano, Antonio (Mercurio Peruano, 2016)
The first circumnavigation of the world by Magellan-Elcano (1519-1522) could not be repeated without causing a serious conflict between Castilla and Portugal. Thus, American historians such as Céspedes del Castillo would affirm, for whom half of the route taken on that journey infringed an agreement signed in 1494 by both kingdoms: the Treaty of Tordesillas. It was therefore vital the location, across the Pacific Ocean, of a route, "la Vuelta de Poniente" to return from the Moluccas to the West Indies, from where spices could re-issued to Europe without infringing any treaty. If Christopher Columbus had known to return successfully on the first attempt of his voyage across the Atlantic Ocean, the return route in the Pacific was not found, after a series of failures, until 1565. The cosmographer Andrés de Urdaneta would be the author of such achievement, completing the route drawing from Europe to Asia by the West, which was the true objective of the Columbian discovery project. His feat will remain in history becoming the biggest exploring success of the reign of Philip II.